Absolute calibration of a three-axis SQUID-cascade vector magnetometer. (8th December 2016) - Schönau, T; Zakosarenko, V; Schmelz, M; Stolz, R; Anders, S; Linzen, S; Meyer, M; Faßbinder, J W E; Meyer, H-G
Abstract: We report on the absolute calibration of a three-axis SQUID-cascade vector magnetometer suited for mobile operation in the Earth's magnetic field. It is based on low temperature superconductor (LTS) dc SQUIDs with sub-micrometer sized cross-type Josephson junctions and exhibits a white noise level of about 10 fT Hz −1/2 . Due to the cascaded operation principle, the huge dynamic range required to resolve a measurement range of more than 50 µ T with sub-pT resolution is split onto several electronic channels of less demanding precision. As a result, the measurement accuracy is less vulnerable to parameter drifts. Furthermore, the intrinsic redundancy of the setup can be used to check for systematic errors of measurement. The offset as well as scaling and directional errors of the magnetometer have been obtained by the method of scalar calibration in our laboratory, resulting in a residuum with a standard deviation of less than 0.64 nT.